PENGEMBANGAN KUESIONER UNTUK MENGANALISIS KEBUTUHAN MAHASISWA TERHADAP LEMBAR KERJA BERBASIS MODEL PEMBELAJARAN IDEA - Yayan Eryk Setiawan; Triwilujeng Ayuningtyas (IKIP Siliwangi, 2021)
This study aims to develop a questionnaire on student needs for worksheets based on the IDEA (Issue, Discussion, Establish, and Apply) learning model that is valid and reliable. This research is development research using 4 stages, namely planning, reconstruction, quantitative analysis, and validation. The result at this planning stage is a questionnaire grid. The result of the reconstruction phase is a questionnaire and scoring guidelines. The results at this quantitative analysis stage were in the form of a questionnaire reliability test using the Alpha Cronbach technique. Reliability test results show that r count > r table, namely 0.927 > 0.423. This means that the questionnaire is reliable. The reliability of this questionnaire also shows that it is in the very high category. The results of the validity test showed that of the 45 questionnaire items, 4 items were invalid and 41 items were valid. Therefore, the results of this study generally obtained 41 questionnaire items of student needs for worksheets based on the IDEA learning model that was valid and reliable. So the questionnaire consisting of 41 statement items can be used to analyze student needs for worksheets based on the IDEA learning model.